Islamic Boarding School Leadership Innovation: From Traditional to Modernization of Education - Salim, Nur Agus; Zaibi, Muhammad; Brantasari, Mahkamah; Ikhsan, Muhammad; Aslindah, Andi (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This research examines leadership innovation at Ibadurrahman Modern Islamic Boarding School, focusing on transitioning from traditional to modern education. The research used a qualitative case study approach, with in-depth interviews, observation, and document analysis. The research findings show that Kiai applies visionary, democratic, paternalistic, and spiritual leadership styles that create an inclusive environment that encourages collaboration and innovation. Democratic leadership enables active participation in decision-making, while paternalistic leadership strengthens the emotional bond between Kiai and staff, creating a harmonious working environment. In addition, the integration of spiritual leadership helps maintain a balance between traditional religious values and modern educational needs. Modernization efforts include adopting technology, multilingual education, and incorporating Islamic perspectives in science, which provide students with essential skills to face global challenges. Conflict management is also done through deliberation, which ensures harmony amid change. In conclusion, leadership innovation at Ibadurrahman Modern Islamic Boarding School successfully bridges tradition and modernity, offering a model for another Islamic boarding school in the face of globalization.